Aid and remittances: their stabilizing impact compared - Patrick Guillaumont; Maëlan Le Goff (Fondation pour les études et recherches sur le développement international (FERDI), 2010)
This paper presents a comparative analysis of the stabilizing effect of official development assistance (ODA) and migrant remittances. First, at the country level and for each kind of flows it assesses their stabilizing impact with regard to the fluctuation of exports, as distinct from their countercyclical character. Most often than the opposite, both kinds of flows appear stabilizing. Second, on a cross-country basis it appears that both aid and remittances dampen the growth volatility. While at the country level, remittances appear to dampen the instability of exports more often than aid does so, on a cross-country basis, aid more than remittances lowers growth volatility.
Keywords: F24; F35; F43; O42; 330; Aide; transferts des migrants